Human Dendritic Cells Express the Complement Receptor Immunoglobulin Which Regulates T Cell Responses - Munawara, Usma; Perveen, Khalida; Small, Annabelle G.; Putty, Trishni; Quach, Alex; Gorgani, Nick N.; Hii, Charles S.; Abbott, Catherine A.; Ferrante, Antonio (Frontiers in Immunology, 2019)
The B7 family-related protein V-set and Ig containing 4 (VSIG4), also known as Z39Ig and Complement Immunoglobulin Receptor (CRIg), is the most recent of the complement receptors to be identified, with substantially distinct properties from the classical complement receptors. The receptor displays both phagocytosis–promoting and anti-inflammatory properties. The receptor has been reported to be exclusively expressed in macrophages. We now present evidence, that CRIg is also expressed in human monocyte-derived dendritic cells (MDDC), including cell surface expression, implicating its role in the adaptive immunity. Three CRIg transcripts were detected and by Western blotting analysis both the known Long (L) and Short (S) forms were prominent but we also identified another form running between these two. Cytokines regulated the expression of CRIg on dendritic cells, leading to its up- or down regulation. Furthermore, the steroid dexamethasone markedly upregulated CRIg expression, and in co-culture experiments, the dexamethasone conditioned dendritic cells caused significant inhibition of the phytohemagglutinin-induced and alloantigen-induced T cell proliferation responses. In the alloantigen-induced response the production of IFNγ, TNF-α, IL-13, IL-4, and TGF-β1, were also significantly reduced in cultures with dexamethasone-treated DCs. Under these conditions dexamethasone conditioned DCs did not increase the percentage of regulatory T cells (Treg). Interestingly, this suppression could be overcome by the addition of an anti-CRIg monoclonal antibody to the cultures. Thus, CRIg expression may be a control point in dendritic cell function through which drugs and inflammatory mediators may exert their tolerogenic- or immunogenic-promoting effects on dendritic cells.